1993
DOI: 10.1143/jjap.32.2962
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling and Atomic Force Microscopy of T4 Bacteriophage and Tobacco Mosaic Virus

Abstract: Bacteriophage T4 and tobacco mosaic virus were imaged by scanning tunneling microscopy after metal coating of the specimens and by atomic force microscopy without coating, and their topographies were examined. A metal coating approximately 5 nm in thickness assured easy and reproducible imaging of samples but obscured their detailed structural features. AFM gave a better resolution on this scale, revealing the presence of tail fibers 2 nm in diameter of T4 phage, which is the best resolution so far reported fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The bacteriophage T4 consists of an elongated icosahedral head, a rod-shaped tail, and a hexagonal baseplate with six fibers . Because it has identifiable structures and well-established dimensions, it has been used as a reference sample to test the image capabilities of AFM. In this paper we show that T4 and its tail are preferentially adsorbed on the CF 3 -terminated surface of these monolayers, which allows mixtures of BSA and T4 to be spatially separated. Moreover, we find that the adsorption of T4 on the CF 3 -terminated surface is sufficiently strong to allow imaging of the bacteriophage by scanning force microscopy and that the resolution in the frictional force mode is significantly higher than that previously achieved in topographical images of T4.…”
Section: Introductionmentioning
confidence: 84%
“…The bacteriophage T4 consists of an elongated icosahedral head, a rod-shaped tail, and a hexagonal baseplate with six fibers . Because it has identifiable structures and well-established dimensions, it has been used as a reference sample to test the image capabilities of AFM. In this paper we show that T4 and its tail are preferentially adsorbed on the CF 3 -terminated surface of these monolayers, which allows mixtures of BSA and T4 to be spatially separated. Moreover, we find that the adsorption of T4 on the CF 3 -terminated surface is sufficiently strong to allow imaging of the bacteriophage by scanning force microscopy and that the resolution in the frictional force mode is significantly higher than that previously achieved in topographical images of T4.…”
Section: Introductionmentioning
confidence: 84%
“…4 Apart from imaging the head and the tail, it was also shown that it is possible to image the tail fibres of phage T4. 5,6,41 By functionalising mica surfaces with amine groups, bacteriophage fd was imaged in liquid. 42 Real time attachment of these particles was followed over 40 min, showing a steady increase in phage adhesion.…”
Section: Imaging Of Viruses and Of Genome Release 31 Afm Imaging Of V...mentioning
confidence: 99%
“…Initial experiments showed hints of DNA release from lysed bacteriophages 4 and the presence of tail fibers. 5,6 Furthermore viral infection of single cells was studied. 7 In the following years the imaging techniques were refined and manipulation of single viruses by AFM became possible as well.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption behavior of tobacco mosaic virus (TMV) on several different self-assembled and Langmuir-Blodgett (LB) monolayers was investigated here to gain insight into the fundamental interactions influencing non-enveloped virus adsorption. While TMV is commonly deposited on surfaces as a size standard in electron and scanning force microscopies (SFM) [5,6], relatively few studies have investigated the adsorption kinetics of this virus, and then, only in a qualitative manner [1,7,8]. In this study the adsorption kinetics of TMV on model substrates are determined quantitatively using total internal reflection fluorescence (TIRF) spectroscopy while the distribution and the aggregation state of adsorbed virus are determined using SFM.…”
Section: Introductionmentioning
confidence: 99%